Probiotics and the microbiota-gut-brain axis: focus on patients with depression. A review of current research - Macrea, Cristina; Ilias, Tiberia; Fratila, Ovidiu; Roxana, Brata; Hocopan, Cristian (Biomedical papers, 2023)
This review covers recent data on the relationship between major depressive disorder (MDD) and faecal microbiome and examines the co-relations between the use of probiotics and changes in psychiatric state. We conducted a thorough search of academic databases for articles published between 2018 and 2022, using specific keywords and previously established inclusion/exclusion criteria regarding faecal microbiota, depressive disorder, and probiotics. Of 192 eligible articles (reviews, original papers, and clinical trials), we selected 10 that fully met our criteria and performed a careful review to determine any correlation between microbiome, probiotic treatment, and depression. All patients were adults (mean age, 36.8), with at least one MDD episode and onset of depression during adolescence (duration of 31.39 years of depressive episodes). We found mixed but mostly positive results regarding the influence of probiotic/prebiotic/postbiotic effects on depression. We could not identify the precise mechanism of action that led to their improvement. Antidepressants did not alter the microbiota, according to studies that evaluated this aspect. Probiotic/prebiotic/postbiotic treatments were proven to be safe, with few and mild side effects. Probiotics seemingly could be beneficial in patients with depression, as evidenced by well-established depression scales. Based on this finding and the high tolerability and safety of probiotics, no caveats against their routine use can be made. Some unmet needs in this field include determination of the dominant type of microbiota in specific patients with depression; study of microbiome-directed/driven treatment regarding dose and duration adjustments; and multiple versus single strain treatments.
Keywords: microbiota; depression; depressive disorder; probiotics